Pengaruh Media, Pelatihan Akademik dan Kenalan Auditor terhadap Stereotipe Auditor: Studi Empiris pada Mahasiswa Akuntansi di Perguruan Tinggi Negeri Kota Padang - Gessa Gessa; Deviani Deviani (Jurnal Eksplorasi Akuntansi, 2024)
The purpose of this study was to determine how the influence of media, academic training, and having auditor acquaintances on auditor stereotypes. The sample in this study were Accounting Students at State Universities in Padang City. Sampling was carried out using purposive sampling technique. The questionnaire was distributed to 332 Accounting Students at State Universities in Padang City. The statistical method used in this research is multiple regression analysis. The results of this study indicate that there is a significant influence of media, academic training, and having auditor acquaintances on auditor stereotypes. The major influence is on academic training as a source of knowledge information about perceptions of the auditor profession being the main information that can reduce the gap between public expectations of the auditor profession and the reality of auditor performance because students' views on audit responsibilities and other professional values change significantly after students take additional audit courses. The implication of this study is that when we have more information about a profession, it will improve our views about the profession and can increase students' intention to enter this profession.